2021
DOI: 10.32607/actanaturae.11067
|View full text |Cite
|
Sign up to set email alerts
|

Super-Enhancers in the Regulation of Gene Transcription: General Aspects and Antitumor Targets

Abstract: Super-enhancers (genome elements that activate gene transcription) are DNA regions with an elevated concentration of transcriptional complexes. These multiprotein structures contain, among other components, the cyclin-dependent kinases 8 and 19. These and other transcriptional protein kinases are regarded as novel targets for pharmacological inhibition by antitumor drug candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
0
5
0
1
Order By: Relevance
“…Recently, studies have shown that super-enhancers are capable of regulating a wide swath of genes. These regions contain elevated levels of transcription factors and display characteristics of active chromatin: monomethylation of lysine at position 4 of histone 3 and acetylation of lysine at position 27 of histone 3 [71]. Super-enhancers have been found in genes involved in T-cell activation (IL2RA/CD25, CD30, and FYN) and known cancer genes (TP73, CCR4, TIAM2, NFATC1, NFATC2, and PIK3R1) in ATL cells [72].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that super-enhancers are capable of regulating a wide swath of genes. These regions contain elevated levels of transcription factors and display characteristics of active chromatin: monomethylation of lysine at position 4 of histone 3 and acetylation of lysine at position 27 of histone 3 [71]. Super-enhancers have been found in genes involved in T-cell activation (IL2RA/CD25, CD30, and FYN) and known cancer genes (TP73, CCR4, TIAM2, NFATC1, NFATC2, and PIK3R1) in ATL cells [72].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are many other factors which potentially affect SE function and change the transcription probability and rate of dependent genes. For example, it is known that massive eRNA transcription from super-enhancers plays an important role during the cis-regulation of target genes [ 12 ]. At the same time, these eRNAs may modulate the expression of distant genes that are not initially associated with studied super-enhancers.…”
Section: Constitutive Super-enhancers In Different Cell Typesmentioning
confidence: 99%
“…Super-enhancers (SE) are described as a cluster of enhancers that have dense assemblies of RNApol II, TFs, and typical enhancer histone modifications (H4K8ac, H3K27ac, and H3K4me) that leads to a greater amount of super-enhancer RNA (seRNA) production ( Figure 2 ) [ 22 ]. The difference between conventional enhancers and SEs is clearly displayed in the nature of the dependence of the transcription activity ensured by the regulatory element and the number of TFs and cofactors associated with it [ 23 ]. The transcription activity at an SE is typically higher than at a distinct enhancer.…”
Section: Biogenesis and Function Of Ernamentioning
confidence: 99%